Root Variation in Tautological Infinitives The Case of Jeremiah - Kjær, Sigrid K. (2020)
The grammatical category of the 'tautological infinitive' occurs throughout the Hebrew Bible but is never more frequent than in the Book of Jeremiah. Three cases of tautological infinitives in the Book of Jeremiah that have been treated as mistakes are reanalyzed in this paper, and new readings are proposed. By examining other instances of tautological infinitives in the Hebrew Bible, this paper argues that the three possible mistakes in Jeremiah are, in fact, part of the book’s general preference for this grammatical construction, and that they do not fall outside the accepted use of the tautology in Biblical Hebrew.